S-band FMCW Radar for target tracking and monitoring - Mohd. Isa, Farah Nadia; Muhd Ariffin, Nor Fatin; Abdul Malek, Norun Farihah; Mohamad, Sarah Yasmin; Mohd. Ramli, Huda Adibah; Asnawi, Ani Liza (Universiti Teknikal Malaysia Melaka, 2018)
A Frequency Modulated Continuous Wave (FMCW) Doppler radar was assembled to detect human as sample target. Its operating frequency is at 2.4GHz with transmitting power of 10.41 dBm. Range resolution of the radar is 2.8 meters at 53.2MHz signal bandwidth and chirp waveform of 40ms. The radar exploits Doppler principle to acquire the range and velocity information of targets whilst a Moving Target Indicator (MTI) pulse canceller is utilized to filter incoming noise signal. With the use of Chirp period-bandwidth product Frequency Modulated (FM) waveform and deramping process, the radars’ Signal to Noise Ratio (SNR) was improved up to 42 dB. The attained maximum range is about 200 meters for a target with Radar Cross Section (RCS) of 1m2 . The constructed radar is capable to measure the speed of moving target at 0.645m/s and above with great accuracy. The radar can detect and determine the position of pedestrians with 0.18% percentage error.